Villains and Victims, but No Workers: Why a prosecution-focussed approach to human trafficking fails trafficked persons - Thiemann, Inga (Anti-Trafficking Review, 2016)
Response to ATR Debate Proposition: ‘Prosecuting trafficking deflects attention from much more important responses and is anyway a waste of time and money’